Classroom Evaluation: Learners’ Perspectives on The Teaching Approach in A Second Language Writing Course - Yuzar, Ella (JETLEE: Journal of English Language Teaching, Linguistics, and Literature, 2022)
Second language writing instructors remain to experience a great deal of difficulty to find the most effective approach for assisting students to the improvement of second language (L2) writing. Teachers might claim that they have provided their students with everything they require and that they have utilized the most effective method for the teaching tasks. By doing an explanatory mixed-method on students’ personal learning experiences, the study suggests that the teachers in the L2 writing subject are to adopt the process-genre approach, by incorporating real-context materials. The teacher also could improve students' understanding of the varieties and functions of text by exposing them to authentic texts. In addition to that, using the process-genre approach, learners might have a more relevant and sensible writing instructions. Therefore, the implementation of a reflection study to evaluate an L2 writing course has yielded valuable information for language instructors, particularly writing instructors, informing them of the most appropriate method to use in the second language classroom.